Quest for power : European imperialism and the making of Chinese statecraft - Halsey, Stephen R., 1975- (Cambridge, Massachusetts : Harvard University Press, 2015)
'Quest for Power analyzes the origins of China's rise to great power status in the twentieth century. The author argues that the threat of European and Japanese imperialism triggered the most innovative state-building efforts since the foundation of the country's last dynasty in the mid 1600s. This claim casts doubt on the entire interpretive thrust of existing historical accounts of China during the late nineteenth and twentieth centuries, questioning their story of decline, weakness, and failure. Halsey instead argues that a military fiscal-state emerged in China between 1850 and 1949 because of the continuing danger of war with the great powers. This form of political organization combined money, bureaucracy, and guns in new ways and helped to ensure the country's survival during the apogee of Western colonialism. As the great powers transplanted their competitive international order to East Asia in the 1800s, China replicated many features of European states through conscious imitation and independent trial and error. Military-fiscal states in these different regions represent variations on a common global theme, their political structures drawn together to a certain extent through a contingent process of historical convergence. Leading officials soon came to describe their reformist policies through a new vocabulary of sovereignty, a European concept that has served as a cornerstone of Chinese statecraft since the late 1860s. In short, China achieved remarkable success in the search for power in the late imperial (1850-1911) and the Republican eras (1911-1949), laying the foundation for its growing international influence since 1949'--Provided by publisher.
Europe's global conquest -- Foreign trade -- Money -- Bureaucracy -- Guns -- Transportation -- Communication -- Epilogue: State-making in China, 1850-1949.
Includes bibliographical references (pages [313]-336) and index.
Keywords: Nation-building -- China -- History; Great powers -- History; Imperialism -- History; China -- Politics and government -- 1644-1912.; China -- Politics and Government -- 1912-1949.; China -- Economic policy; China -- Military policy; Europe -- Colonies -- Asia -- History; Europe -- Foreign relations -- 1871-1918.; Europe -- Foreign relations -- 1918-1945.